Modellbasierte Entwicklung eines aktiven Sicherheitssystems für elektrifizierte Fahrräder - Maier, Oliver (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
The electrical energy on electrified bicycles offers new functional possibilities such as an active safety system to assist the rider during the braking process. This work shows the technical feasibility of such a system by presenting a rideable prototype. The so-called braking dynamics assistance system prevents the cyclist from both front wheel lockup and rollover (along the vehicle's transverse axis).